Guttate hypopigmentation in Darier disease: A rare presentation - Aradhana Rout; Ashish Kumar Pandey; Karthi Kishore (Pigment International)
Darier disease (DD) is an autosomal dominant genodermatosis attributed to ATP2A2 gene mutation which encodes the sarco/endoplasmic reticulum Ca2+ATPase isoform 2. Due to variable gene expressivity, the clinical manifestations are often atypical and of varied severity. The classical feature of DD is the presence of firm yellowish brown flat to hyperkeratotic papules in a seborrheic distribution. Cobblestoning of oral mucosa and V shaped nicking of nails are also important associated findings of DD. Herein, we report a 35-year-old male patient with guttate leukoderma as a presenting feature of Darier disease with its clinical, histopathological, and dermoscopic findings.